Effects of Applying Organic Amendments on Soil Aggregate Structure and Tomato Yield in Facility Agriculture - Wen-Qu Tao; Qian-Qian Wu; Jie Zhang; Ting-Ting Chang; Xin-Na Liu (Plants)
Amendment significantly improves soil structure and promotes crop growth. To combat soil degradation and low crop yields in facility agriculture, it is crucial to study the optimal application rate of amendments. This study analyzed the effects of biochar, vermicompost, and mineral-source potassium fulvic acid on the stability of aggregate structure, soil nutrient content, and tomato yield in cambisols, providing a theoretical basis for improving the soil quality of plastic greenhouses in Southern China. A pot experiment on tomato cultivation was carried out in yellow-brown soil in plastic greenhouses. The experiment included eight treatments: 1% biochar (B1); 3% biochar (B3); 5% biochar (B5); 3% vermicompost (V3); 5% vermicompost (V5); 0.1% mineral-source potassium fulvic acid (F1); 0.2% mineral-source potassium fulvic acid (F2); and the control condition without adding soil amendments (CK). The results showed that the biochar and vermicompost treatments effectively reduced soil bulk density and increased total soil porosity. Compared to the control, treatments with soil amendments significantly increased soil pH and had different effects on soil nutrients: F2 showed the most significant improvement in the content of available nitrogen, available phosphorus, and available potassium, with an increase of 133.33%, 834.59%, and 74.34%, respectively; B3 treatment had the highest increase in dissolved organic carbon (DOC), while B5 treatment had the highest organic matter content. Compared to the CK, the particle size of the biochar treatment was mainly 0.053~0.25 mm, while the V3, F1, and F2 mainly occurred with a particle size > 0.25 mm; and V3 has the best aggregate stability. Biochar, vermicompost, and mineral potassium fulvic acid can all promote tomato yield, with the F2 and V3 treatments having a yield increase effect of over 30%. Furthermore, Pearson’s correlation analysis showed a highly significant positive correlation between geometric mean diameter (GMD) and mean weight diameter (MWD), water-stable macroaggregate content (R0.25), and a positive correlation between alkaline-dissolved nitrogen, available phosphorus, dissolved organic carbon content, and aggregate stability indicators. Adding 0.2% mineral-source potassium fulvic acid optimizes cambisols’ properties, enhances aggregate formation and stability, boosts tomato yield, and shows great application potential.